Ethos e antiethos no discurso político eleitoral de José Serra (PSDB) no HGPE/TV da eleição presidencial de 2010 no Brasil - Arcine, Raquel de Freitas (2012)
In this research, we reflect about the question of contemporary political and media discursive practices, having as discursive object of analysis the operation of the controversial constitution of ethos and antiethos present in the political election campaign of José Serra, in the Free Electoral Advertising (Horário Gratuito de Propaganda Eleitoral - HGPE / TV), from discursive place of a candidate who disputed the Brazilian presidential elections in 2010. Political discourse has been the subject of much research in the media, especially television, has influenced policy, causing it to acquire new ways. We observed that changes in politics, due to rapid technological development of the media, have changed the landscape of political campaigns. Thus, new formats appear on the political scene, as the Free Electoral Advertising (HGPE) and the election debates, which were forced to adapt to television language. In this context, this study intends to face the challenges of describing the operation of political discourse in its contemporary setting, in which the TV, for the representation of its speech can be used a combination of three codes: the visual; the linguistic and the sound, which enhance the effects of truth, intended by the political discourse. Thus, our main objective is to describe the process of ethos and antiethos construction, while elements of the global semantic system of political-electoral discursive formation which joins the political subject José Serra. More specifically, we aim at understanding how the process of José Serra's ethos and antiethos construction, raising hypotheses about the reasons for any failures in this discursive ritual, whether on the one hand, for leading negative meanings for yourself , whether on the other excesses in the disqualification of his political opponent, who was elected president of Brazil, Dilma Rousseff. Thus, one of our challenges, besides bringing forth ideas and propositions that can motivate thinking subjects, improve their point of view, understand and react to political events surrounding them, is to provide opportunities for discussion and further reflection, mainly around the concept of antiethos, vaguely described in the linguistical-discursive literature to which we have studied. Based on then studies of discursive ethos and antiethos proposed by Maingueneau (1997, 2008), in studies of Discourse Analysis (DA) about the political discourse, with the contribution of studies of political communication, we cut out the file of twelve videos from the José Serra's HGPE in the second round of presidential elections, significant discursive sequences present in the program were transcribed, in which we show that José Serra takes and silences memories and themes to build his ethos and at the same time, do not let his antiethos stands out. Simultaneously, the ideological effect of his form-subject, it is possible to see that constantly, Serra needs to deconstruct the image of the opposing candidate Rousseff (PT), showing through the theme "history/political career," among others, that she (Dilma Rousseff) would not be prepared to govern the country, but he (José Serra) would. However, by constantly attacking his opponent, Serra produces an antiethos for himself through failure in discursive ritual, along with the excessive presence of justification discourses.